A heterogeneidade da demanda em modelos evolucionários: um ensaio teórico e o caso da indústria farmacêutica - Thiago Caliari Silva (2014)
The present dissertation aims to discuss the relevance of the bounded rationality and heterogeneity of demand in evolutionary models. The proposed model seeks to do a connection between a model of technological complexity (pNK model) and a model of demand heterogeneity (Take-the-Best model) to show how the different considerations about the ordering and definition of consumer preferences associate to limitations on the set of information can explain the dynamics of the fluctuations of the outcome variables of industrial firms. To this work, they were defined two applications with the purpose to exploring some analytic potential of the constructed model. First, in a theoretical model, it is showed how changes in consumer behavior affect the market share of innovative firms. Second, and more importantly, a History-Friendly model uses empirical information about the pharmaceutical industry, focusing on the Brazilian specifications, to demonstrate how behavioral changes in demand influence and explain the conduct and performance of industrial firms, shaping the dynamics structure that can be observed in empirical studies.